2004
DOI: 10.1097/00004694-200407000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Displaced Type II Extension Supracondylar Humerus Fractures

Abstract: The treatment of a displaced type II extension supracondylar humerus fracture is controversial. Many authors recommend that all displaced type II fractures be surgically pinned. The purpose of this study was to determine the success of reduction and casting (without pinning) in maintaining the alignment of type II fractures. Of the 25 elbows that underwent an initial reduction in the emergency room, 18 (72%) maintained alignment. Seven fractures lost position, and five of the seven patients underwent secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 8 publications
2
21
0
1
Order By: Relevance
“…We found 28 studies examining outcome data of closed reduction and casting for displaced supracondylar fractures. 17–43 This included any method of immobilisation whereby plaster of Paris was applied to the injured arm, set under any degree of flexion. Closed reduction was performed and, where specified, manipulation of the displaced injury was performed under general anaesthetic, local block or sedation.…”
Section: Resultsmentioning
confidence: 99%
“…We found 28 studies examining outcome data of closed reduction and casting for displaced supracondylar fractures. 17–43 This included any method of immobilisation whereby plaster of Paris was applied to the injured arm, set under any degree of flexion. Closed reduction was performed and, where specified, manipulation of the displaced injury was performed under general anaesthetic, local block or sedation.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal treatment for Gartland type 2 fractures has been historically widely debated. In 1991 Ippolito and Perugia 40 reported good results with trans-olecranic traction and casting; more recently Parikh et al 41 and Spencer et al 42 showed how closed reduction and casting is a safe and effective treatment, as well as other authors 13 stated that pinning all type 2 fractures would result in 77% of unnecessary surgery.…”
Section: Discussionmentioning
confidence: 97%
“…One of the four groups who treat children with supracondylar humerus fractures within our city prefers to treat the majority of extension type II fractures with closed reduction and cast immobilization in the emergency department and then close follow-up to determine the need for surgery, while the other practices typically favor planned delayed closed reduction and percutaneous pinning. Operative and nonoperative treatment are both supported in the literature [ 4 , 5 , 7 9 , 13 , 15 , 30 ], although operative management is advocated by the AAOS [ 3 ]. While some may argue that surgical treatment is not required to manage these fractures due to satisfactory long-term results [ 31 ], the need for close follow-up is still important to avoid loss of reduction and malunion in either treatment method, as long-term angular deformity can result in symptomatic cubitus varus or loss of flexion [ 2 , 27 – 29 , 32 38 ].…”
Section: Discussionmentioning
confidence: 99%